Pengukuran dan Penentuan Prioritas Perbaikan Kualitas Layanan Jasa Service Kendaraan dengan Metode Service Quality dan Analytical Hierarchy Process - Krisnadhi Hariyanto; Astria Hindratmo (Journal of Research and Technology, 2020)
The service business in Indonesia is growing every year and competition is getting tougher. One of the service businesses that is always growing is motor vehicle repair service. So that the vehicle service company must make service improvements to be able to compete. For this reason, the company needs to know the service performance so that the company must know the advantages and disadvantages of the services provided to customers. The purpose of this study is to measure the performance of vehicle service quality and determine service improvement priorities in increasing customer satisfaction and loyalty. The method used in this research is service quality and Analytical Hierarchy Process (AHP). The results of the study were to obtain 21 service attributes obtained from interviews. Then from the results of processing with the service quality method, it turns out that there is a gap in service quality based on perceptions and expectations because it is negative. So all the existing service attributes need to be improved. Meanwhile, the results of determining priorities that need to be improved on the 21 service attributes using the AHP method show that the mechanical speed attribute in car service is the first priority because it has the largest weight, namely 0.107. Then the service attribute that gets the last priority to be repaired is the equipment and equipment attribute with the smallest weight of 0.02 because the current dealer already has a fairly complete vehicle service tool.